Diabetes and calcification: The potential role of anti-diabetic drugs on vascular calcification regression. (August 2020) - Ghosh, Sounak; Luo, Dongling; He, Wanbing; Chen, Jie; Su, Xiaoyan; Huang, Hui
Graphical abstract: Abstract: Vascular calcification (VC) has been well-established as an independent and strong predictor of cardiovascular diseases (CVD) as well as major cardiac adverse events (MACE). VC is associated with increased mortality in patients with CVD. Pathologically, VC is now believed to be a multi-directional active process ultimately resulting in ectopic calcium deposition in vascular beds. On the other hand, prevalence of diabetes mellitus (DM) is gradually increasing thus making the current population more prone to future CVD. Although the mechanisms involved in development and progression of VC in DM patients are not fully understood, a series of evidences demonstrated positive association between DM and VC. It has been highlighted that different cellular pathways are involved in this process. These intermediates such as tumor necrosis factor alpha (TNF-α), various interleukins (ILs) and different cell-signaling pathways are over-expressed in DM patients leading to development of VC. Thus, considering the burden and significance of VC it is of great importance to find a therapeutic approach to prevent or minimize the development of VC in DM patients. Over the past few years various anti diabetic drugs (ADDs) have been introduced and many of them showed desired glucose control. But no study demonstrated the effects of these medications on regression of VC. In this review, we will briefly discuss the current understanding on DM and VC and how commonly used ADDs modulate the development or progression of VC.